USE OF E-LEARNING AND COURSE ASSIGNMENTS TO IMPROVE LEARNING EFFECTIVENESS IN CONSTRUCTION PROJECT PLANNING - Tseng, Hao (PEOPLE: International Journal of Social Sciences, 2019)
Construction project planning integrates various types of theoretical knowledge and practical skills in civil engineering, and learning effectiveness among students is often diminished by a lack of real construction work experience. This research describes the design of a series of course assignments for construction project planning instruction, integrated with the use of e-learning tools. Following the semester-long course, a questionnaire is used to assess learning outcomes. Findings show that the course assignments significantly improve learning outcomes and that learners find the e-learning tool to be convenient and helpful in developing autonomous learning abilities through solving course assignment problems. In addition, as smart phones have emerged as a mainstream e-learning device, the user interface of instructional content must be modified for optimal effectiveness on smart phones. The research findings are integrated and enumerated as an instructional framework reference for the subject of Construction Project Planning.